The Effect of an Innovative Vision Simulator (OrCam) on Quality of Life in Patients with Glaucoma. (July 2019) - Waisbourd, Michael; Ahmed, Osama M.; Newman, Joshua; Sahu, Malya; Robinson, Debbie; Siam, Linda; Reamer, Courtney B.; Zhan, Tingting; Goldstein, Michaella; Kurtz, Shimon; Moster, Marlene R.; Hark, Lisa A.; et al.
Purpose: The aim of this study was to determine the impact of OrCam on vision-related quality of life of patients with legal blindness and end-stage glaucoma. OrCam is a device comprised of a camera and earpiece attached to the user's eyeglass that translates written text to speech. Methods: In this prospective, observational study, a total of 27 participants were recruited and tested. All participants were legally blind. Participants were provided with the OrCam device during the study period and trained how to operate it. National Eye Institute Visual Functioning Questionnaire-25 (NEI-VFQ-25) and other questionnaires were given to participants at the baseline visit and at the end of the 4-week study for comparison. Additional questions were surveyed weekly during the study to monitor progress. Results: At the final visit after 1 month, most participants, 74.1% ( n = 20/27), reported an increase in their overall quality of life. Participants were highly satisfied with the device; 88.9% ( n = 24/27) reported being "very satisfied" or "satisfied" with the device. The NEI-VFQ-25 near vision subscale score improved from 29.9 to 37.2 ( p = .045). Discussion: OrCam allowed participants with legal blindness to read independently when in controlled settings, subsequently improving their quality of life. However, users had more difficulty using the device when the location of text was not readily apparent (e.g., street signs, billboards), and users with some degree of vision had an easier time aligning the device with the text. Implications for practitioners: This device may offer participants with visual impairments the opportunity to read independently.